2010
DOI: 10.1016/j.physbeh.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Women with PTSD have lower basal salivary cortisol levels later in the day than do men with PTSD: A preliminary study

Abstract: Acute stress responses of women are typically more reactive than that of men. Women, compared to men, may be more vulnerable to posttraumatic stress disorder (PTSD). Whether there are differences between women and men with PTSD in levels of the stress hormone, cortisol, was investigated in a pilot study. Methods women (n=6) and men (n=3) motor vehicle accident (MVA) survivors, with PTSD, had saliva collected at 1400 h, 1800 h, and 2200 h. Cortisol levels in saliva were measured by radioimmunoassay. An interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Differences in inflammatory cytokine levels in trauma survivors with PTSD have previously been reported (Gill et al, 2009). Discrepancies may potentially reflect different degrees of HPA axis response suppression to glucocorticoid activation (Freidenberg et al, 2010), or alternatively, differences associated with the duration since the traumatic experience as well as other confounding factors. One study examining the levels of inflammatory markers within a refugee population with PTSD postulated that differences could partly be explained by a variable environmental component associated with less antigen exposure (Söndergaard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in inflammatory cytokine levels in trauma survivors with PTSD have previously been reported (Gill et al, 2009). Discrepancies may potentially reflect different degrees of HPA axis response suppression to glucocorticoid activation (Freidenberg et al, 2010), or alternatively, differences associated with the duration since the traumatic experience as well as other confounding factors. One study examining the levels of inflammatory markers within a refugee population with PTSD postulated that differences could partly be explained by a variable environmental component associated with less antigen exposure (Söndergaard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that women with PTSD have lower cortisol levels than their healthy counterparts, an effect not observed in men [67; 68]. Although not always replicated, these results do suggest that, in some cases, low cortisol levels distinguish women with PTSD from those without [69; 70].…”
Section: Sex Differences In Neuroendocrine Responses To Stressmentioning
confidence: 95%
“…Decreased basal levels of circulating (Yehuda et al, 2005) and urinary free cortisol (Mason et al, 1986) have been described in individuals with PTSD. However, studies have also found increased or no differences in basal glucocorticoid levels (Meewisse et al, 2007) and diurnal cortisol rhythms in individuals with PTSD (Freidenberg et al, 2010;Maes et al, 1998), suggesting that other factors maybe be contributing to HPA dysregulation in PTSD, such as sex (Freidenberg et al, 2010), type and duration of trauma exposure, and severity of PTSD symptoms (Shea et al, 2005). Regardless of the equivocal nature of findings describing differences in basal cortisol levels in individuals with PTSD, more consistent are the findings that PTSD is associated with enhanced glucocorticoid negative-feedback inhibition of the HPA axis as evidenced by increased suppression of cortisol levels following a dexamethasone-suppression test (Yehuda et al, 1995).…”
Section: Mechanisms Of Increased Inflammation In Fearand Anxiety-basementioning
confidence: 99%